China clay as an adsorbent for dye house wastewaters - Gupta G.S.; Prasad G.; Singh V.N. (My University, 2025)
The ability of china clay to remove a popular chrome dye, Omega Chrome Red ME, from aqueous solutions has been studied. Maximum removal (i.e., 81.08%) was noted at 10 mg l−1 initial dye concentration, 53μm adsorbent particle size, 2.0 pH and 303 K. The process follows a first order rate kinetics. Intraparticle diffusion and mass transfer coefficients have been determined at different temperatures. The adsorption data fits well in the Langmuir adsorption model. The effect of temperature has been examined on the basis of boundary layer thickness and enthalpy change studies. Heat of adsorption has been found to be a function of surface coverage. The maximum removal of the dye in acidic range has been explained on the basis of surface hydroxylation, acid‐base dissociation and surface complexation probabilities. A 100% desorption of the dye from the adsorbent surface was noted at pH 12.0. © 1992 Taylor and Francis Group, LLC.